LEGAL NATURE OF RELATIONS IN CIVIL AVIATION - Husar, Olha; Tekyedzhanova, Kristina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to study and analyze part of public legal relations as a separate category arising in the field of civil aviation as to their legal nature. Research methods: the study is based on general scientific methods and methods of cognition. The methodological basis is objectivity and a combination of critical and constructive approaches. Results: the theoretical meaning of the concept of "legal nature" is defined, the necessity of establishing the legal nature of relations in the field of civil aviation is substantiated. The place of relations in the structure of public law is established. Нe substantive content of legal relations in the field of civil aviation refers to the actual behavior that the entitled party can perform, and the obligated party must perform. The legal content of legal relations means the subjective rights and legal duties of the parties enshrined in the rules of law. At the same time, legal relations in the field of civil aviation may arise, change and terminate on the basis of legal facts, which may include legal acts, acts of management; offenses (norms of administrative, civil, criminal law, etc.) in the field of air transport. Discussion: the study of the legal nature of relations in the field of civil aviation is determined by the peculiarities of the theoretical understanding of their content and essence and the definition of sectoral affiliation to public law. It is stated that the subjects of legal relations in civil aviation are a system. All elements of the system interact in the process of performing their functions at different levels. They are united by a common goal and contribute to the comprehensive development and safety of civil aviation. Legal relations in the field of civil aviation, which arise in the implementation of various activities, form a qualitatively homogeneous system of social relations regulated by the rules and principles of national and international law. These legal relationships are multifaceted in their content, form, development, as well as the conditions under which they function.